Pengaruh Latihan Handstand Terhadap Peningkatan Keseimbangan Statis Pada Anak Laki-Laki Usia 8-9 Tahun Di SDN 2 Getas Blora Jawa Tengah - Anggraini, Fenti Siska; , Totok Budi Santoso, S.Fis., MPH; , Yulisna Mutia Sari, SSt.FT., M.Sc () (2016)
Background: Growth during the period between 6-9 years old so quickly, most children reach a mature pattern through gross motor skills, and posture and balance them to be better. The balance has a variety of very important factor, so that the balance factor here is very great role in children in sports activities and in everyday life. The development of static balance in boys aged 8-9 years have not improved. Static balance is the ability to maintain a balanced state of body is at rest. Balance exercises are very important for children because this exercise was helpful to the body in order to be stable when doing daily activities Objective: To determine the effect of exercise handstand against the increase in static equilibrium in boys aged 8-9 years. Methods: This research uses a method Quasi Experiment with Pre and Post Test With Control Group Design. Sampling technique is purposive sampling. Respondents of this study as many as 24 people, with 11 people in treatment group, and 13 people as a control group. This research was conducted 12 times at 4-week treatment. Measurement balance using Stork Stand Test. Results: The results of static balance in the treatment group showed significant namely p = 0.003 or p <0.05. The research of static equilibrium in the control group p = 0.422 or p> 0.05. The results of the effect of different treatment group and the control group p = 0.000 or p <0.05. Conclusion: There is a handstand exercise influence on the increase in static equilibrium in boys aged 8-9 years in the treatment group. And there is a significant difference in static equilibrium in the treatment group are given exercises handstand with a control group that was not given any treatment.